Marcelo in the Real World - Stork, Francisco X. (New York : Arthur A. Levine Books, 2009)
Marcelo Sandoval, a seventeen-year-old boy on the high-functioning end of the autistic spectrum, faces new challenges, including romance and injustice, when he goes to work for his father in the mailroom of a corporate law firm.
Keywords: Autism -- Fiction; Asperger's syndrome -- Fiction; Interpersonal relations -- Fiction